THE EFFECTIVENESS OF THE SQUAT EXERCISE MODEL ON PHYSIOLOGICAL CHANGES IN X-FOOT PATIENTS AT EVITA SPORT CONSULTANT AND THERAPY - Evitamala, Lilik; Hasbi, Hasbi; Syahroni, Mohammad (STKIP Melawi, 2024)
Abstract: Feet are an important part of the human body. The feet support the body's weight and are used for walking. If the legs experience problems, other parts of the body will feel the impact. One of the problems with the feet is X-shaped feet. Through physical exercise, people's physical fitness will increase so that it can support optimal performance. The form of training to gain leg muscle strength in weight training is squatting. Squat training is a type of weight training to increase the development of strength, especially in the leg muscles, and weights are the main basis for training. The type of research used is quasi-experimental. The subjects in this research were 12 Police Academy Candidates at Evita Sport Consultan and Therapy. Because the population was relatively small, the entire population was sampled using total sampling techniques. The variable in this research is the physiological changes in sufferers of Foot The initial test is taken before being given treatment or before being given any form of training through a prepared training program. The hypothesis proposed in this research is that there is an effectiveness of the Squat Training Model on the Physiological Changes of X-Leg Sufferers at Evita Sport Consultan and Therapy.Keywords: Training Models, Squats, Physiological Changes, and X-Legs Abstrak: Kaki merupakan bagian penting dari tubuh manusia. Kaki menopang berat badan dan digunakan untuk berjalan. Jika kaki mengalami masalah, maka bagian tubuh lainnya pun akan ikut merasakan dampaknya. Salah satu masalah pada kaki adalah kaki berbentuk X. Melalui latihan jasmani maka kebugaran jasmani masyarakat akan meningkat sehingga dapat menunjang kinerja yang optimal. Bentuk latihan untuk menambah kekuatan otot tungkai pada latihan beban adalah jongkok. Latihan jongkok merupakan salah satu jenis latihan beban untuk meningkatkan perkembangan kekuatan terutama pada otot kaki, dan beban merupakan landasan utama dalam latihan. Jenis penelitian yang digunakan adalah eksperimen semu. Subyek dalam penelitian ini adalah 12 orang Calon Akpol di Evita Sport Consultan and Therapy. Karena populasinya relatif kecil, maka seluruh populasi dijadikan sampel dengan menggunakan teknik total sampling. Variabel dalam penelitian ini adalah Perubahan Fisiologis Penderita Kaki. Tes awal dilakukan sebelum diberikan pengobatan atau sebelum diberikan pelatihan dalam bentuk apapun melalui program pelatihan yang telah disiapkan. Hipotesis yang diajukan dalam penelitian ini adalah terdapat Efektivitas Model Latihan Squat Terhadap Perubahan Fisiologis Penderita X-Leg di Evita Sport Consultan and Therapy.Kata Kunci: Model Latihan, Squat, Perubahan Fisiologis, Kaki X